1988
DOI: 10.1103/physrevb.38.13133
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-concentation-dependent electronLO-phonon coupling observed in GaAs-(Ga,Al)As heterojunctions by resonant-polaron cyclotron resonance

Abstract: The cyclotron resonance (CR) of the two-dimensional electron gas (2D EG) in GaAs-(Ga, A1)As heterojunctions has been studied in the resonant-polaron regime for 2D carrier densities N, in the range (0.8-5.4) && 10" cm . A reflectivity technique has allowed the CR to be recorded at energies up to 35.63 meV, within the GaAs reststrahlen band, and a calculation of the dielectric response of the complete heterostructure has enabled the effective masses to be reliably evaluated from the line shapes and positions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…This leads to a resonant splitting of this transition, the so-called resonant polaron effect, which has been studied for several decades in bulk semiconductors 2,3 and more recently in low-dimensional systems. [4][5][6] Most of the studies reported so far have focused on weakly polar materials, such as InSb ͑Fröhlich constant ␣Ϸ0.02) or GaAs (␣Ϸ0.07). In such materials, the polaron splitting is small ͑of the order ␣ 2/3 ប LO , see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to a resonant splitting of this transition, the so-called resonant polaron effect, which has been studied for several decades in bulk semiconductors 2,3 and more recently in low-dimensional systems. [4][5][6] Most of the studies reported so far have focused on weakly polar materials, such as InSb ͑Fröhlich constant ␣Ϸ0.02) or GaAs (␣Ϸ0.07). In such materials, the polaron splitting is small ͑of the order ␣ 2/3 ប LO , see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…65,67,69,70,8 ' 1 Cyclotron-resonance measurements was also reported for wide (0.1 -0.3 um) modulation-doped Al^Ga^As graded parabolic quantum wells for electron areal densities n s =10 9 -2.5x10" cm" 2 . 75 A clear dependence of the cyclotron frequency on n, was observed in the extreme quantum limit which was understood in terms of alloy effects.…”
Section: (B) Temperature and Pressure Effectsmentioning
confidence: 82%
“…where K 2 is a parameter describing the slope of the effective mass when plotted as a function of energy, m 0 is the band edge effective mass, ͗T z ͘ is the kinetic energy due to the shape of the 2DES confinement potential, E g the GaAs band gap, and E CR ϭប c Ϯg* B B the cyclotron energy. [26][27][28][29] The splitting has a characteristic B 2 dependence because the magnetic field enters both the cyclotron separation between the Landau levels and the g factor difference between the ground and first Landau level. 26,27 If the electrons do not interact and behave as a classical gas of single particles, the CR spectrum of a 2DES should be identical to that found in high-purity, low carrier concentration bulk GaAs.…”
Section: Resultsmentioning
confidence: 99%